Phase-of-Play Performance Profiles in Elite Women’s Futsal: Evidence from the FIFA Women’s Futsal World Cup 2025 - Nufi Saidatus Tsaniyah; Achmad Widodo; Irmantara Subagio; Heri Wahyudi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. The purpose of this study was to analyze performance characteristics associated with in-possession, out-of-possession, and transition phases during the FIFA Women’s Futsal World Cup 2025. As the inaugural edition of this global tournament, the study aimed to establish baseline phase-of-play performance profiles at the highest level of women’s futsal competition. Materials and methods. A descriptive quantitative research design using a notational performance analysis approach was employed. The sample consisted of 64 team performances derived from all 32 matches of the FIFA Women’s Futsal World Cup 2025. Performance data were obtained from official match summary reports released by the tournament organizers. Performance indicators were categorized according to phases of play, including in-possession, out-of-possession, and transition actions. Descriptive statistics, including total counts, mean values with standard deviations, and relative frequencies, were calculated using SPSS statistical software. Results. Out-of-possession actions accounted for the largest proportion of total team actions (50.8%), followed by in-possession actions (41.0%), while transition actions represented a smaller share (8.2%). In-possession performance was dominated by set plays, which accounted for 55.3% of actions within the phase, indicating a strong reliance on structured offensive situations. Out-of-possession behaviors were primarily characterized by mid-block and low-block defensive organization, reflecting an emphasis on compact defensive structures. Transition phases were mainly composed of recovery and defensive transition actions, highlighting the importance of reorganization following possession changes. Conclusions. Performance at the FIFA Women’s Futsal World Cup 2025 was characterized by a high volume of out-of-possession activity, structured in-possession behaviors dominated by set plays, and transition phases focused primarily on recovery and defensive reorganization. These findings provide the first phase-of-play performance benchmarks at the world championship level in women’s futsal and offer valuable reference values for coaches, performance analysts, and researchers preparing for future international competitions.